Fasting inhibits excitatory synaptic input on paraventricular oxytocin neurons via neuropeptide Y and Y1 receptor, inducing rebound hyperphagia, and weight gain - Wang, Lei; Suyama, Shigetomo; Lee, Samantha A.; Ueta, Yoichi; Seino, Yutaka; Sharp, Geoffrey W. G.; Yada, Toshihiko (Frontiers in Nutrition, 2022)
Fasting with varying intensities is used to treat obesity-related diseases. Re-feeding after fasting exhibits hyperphagia and often rebound weight gain. However, the mechanisms underlying the hyperphagia and rebound remain elusive. Here we show that 24 hours food restriction (24h FR) and milder 50% FR, both depress synaptic transmission in the hypothalamic paraventricular nucleus (PVN) and induce acute hyperphagia in rats. 24h FR is followed by weight rebound but 50% FR is not. Orexigenic neuropeptide Y (NPY) via the Y1 receptor (Y1R) inhibited the miniature excitatory postsynaptic current (mEPSC) on anorexigenic oxytocin neurons in the PVN. 24h FR and 50% FR activated this neuronal pathway to induce acute hyperphagia on Days 1~3 and Days 1~2 after FR, respectively. 24h FR induced large mEPSC depression, recurrent hyperphagia on Days 9~12 and rebound weight gain on Days 12~17, whereas 50% FR induced moderate mEPSC depression and sustained weight reduction. Transverse data analysis on Day 1 after 24h FR and 50% FR demonstrated saturation kinetics for the mEPSC depression-hyperphagia curve, implying hysteresis. The results reveal FR-driven synaptic plasticity in the NPY-Y1R-oxytocin neurocircuit that drives acute hyperphagia. FR with the intensity that regulates the synapse-feeding relay without hysteresis is the key for successful dieting.